2014
DOI: 10.1016/j.bjp.2014.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic accumulation of sesquiterpenes in essential oil of Pogostemon cablin

Abstract: Essential oil GC-MS Patchouli alcohol Pogostemon cablinSesquiterpenes A B S T R A C T Essential oil produced by patchouli was one of the most important naturally occurring base materials used in the perfume industry, containing various sesquiterpenes. Three different parts (leaves, stems and roots) of Pogostemon cablin (Blanco) Benth., Lamiaceae, were profiled in relation to different maturation phases in this paper, evaluating the variations in content of the major sesquiterpenes in the essential oil. Twelve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 21 publications
1
21
0
Order By: Relevance
“…The average oil percentage in “dried” P. cablin leaves as reported in 72 references was calculated as 2.6% (ranges: 0.54 – 5.2%) . However in view of the discussion below, this figure is not precise as it is dependent on the exact plant material used (cultivar, age, soil and growth conditions), percentage of stems as well as foreign materials (soil, other plant species like weeds), drying and/or fermentation, storage, final percentage of water and the distillation technique, conditions and duration.…”
Section: Influence Of Fertilisation Harvesting Time Drying Fermentmentioning
confidence: 99%
“…The average oil percentage in “dried” P. cablin leaves as reported in 72 references was calculated as 2.6% (ranges: 0.54 – 5.2%) . However in view of the discussion below, this figure is not precise as it is dependent on the exact plant material used (cultivar, age, soil and growth conditions), percentage of stems as well as foreign materials (soil, other plant species like weeds), drying and/or fermentation, storage, final percentage of water and the distillation technique, conditions and duration.…”
Section: Influence Of Fertilisation Harvesting Time Drying Fermentmentioning
confidence: 99%
“…Genotype effects were also observed in chicory forage, because cultivars with higher STL than others maintained the characteristics regardless of the growth sites (Foster et al, 2006). Chicory studies also report STL content variation with organ developmental stage, cultivation and geo-localisation that account for GxE effects (Peters et al, 1997; Foster et al, 2006; Ramirez et al, 2013; Chen et al, 2014). The higher content of DHLc, DHdLc and Lp in Mol vs. Gal may account for bitterness differences.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study revealed that the patchoulol content in leaf oil (37.5–51.0%) of P . cablin from Hainan Province is higher than that in stem oil (28.2–42.0%) and root oil (14.6–35.1%) (Chen et al ), suggesting that leaves and stems are the optimal tissues for commercial use. Furthermore, patchoulol content in the leaves and stems increase with aging (Luo et al , Chen et al ).…”
Section: Introductionmentioning
confidence: 99%
“…cablin from Hainan Province is higher than that in stem oil (28.2–42.0%) and root oil (14.6–35.1%) (Chen et al ), suggesting that leaves and stems are the optimal tissues for commercial use. Furthermore, patchoulol content in the leaves and stems increase with aging (Luo et al , Chen et al ). Recently, compartmental expression of key genes in tobacco (Wu et al ) and Physcomitrella patens (Zhan et al ) significantly improved patchoulol content, which amounts to the level of patchoulol observed in P .…”
Section: Introductionmentioning
confidence: 99%